3D characterization by tomography of beta Al9Fe2Si2 phase precipitation in a Al6.5Si1Fe alloy. Issue 1 (March 2016) - Ferdian, D; Salvo, L; Lacaze, J; Tenailleau, C; Duployer, B; Malard, B
Abstract: The microstructure evolution of beta phase during solidification of a synthetic Al6.5Si1Fe (wt.%) alloy has been investigated by in-situ synchrotron micro-tomography and post-mortem tomography. In-situ solidification was observed at a constant cooling rate of 10°C min -1, from above the alloy's liquidus with the melt at 618°C down to 575°C which is just above the (Al)-Si-beta invariant eutectic reaction. Primary (Al) dendrites nucleated at 608°C, followed by the formation of beta-Al9 Fe2 Si2 phase starting at 593°C. After a rapid growth stage until 587°C as thin plates, beta phase continued to grow at a paced rate. Thickening of the plates was also evaluated and it was observed that the decrease in the lateral growth rate of the plates did not lead to an increase of their thickening rate. It was noted that the interconnectivity between beta precipitates increased as the solidification progressed. While nucleation of beta phase has previously been reported to occur on the alumina scale formed at the outer surface of the material, it is shown from post mortem tomography that bulk nucleation can occur as well.